2014
DOI: 10.1002/cctc.201300958
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships of Nickel–Hexaaluminates in Reforming Reactions Part II: Activity and Stability of Nanostructured Nickel–Hexaaluminate‐Based Catalysts in the Dry Reforming of Methane

Abstract: Ni–hexaaluminates exhibiting a high magnetoplumbite or β“‐alumina phase content (>80 wt %) and high specific surface areas (10–30 m2 g−1) were investigated under dry reforming conditions. Ni content and choice of mirror plane cation are the key factors controlling the structure–property relationship in the dry reforming reaction of CH4. The Ni content is favorably kept below a threshold of y=0.25 in ANiyAl12‐yO19−δ, (A=Ba, La, Sr) to ensure controlled nanoparticle formation and to avoid uncontrolled Ni0 nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In general, these trends suggest that high conversions to syngas and representative H 2 /CO ratios are expected at the industrially relevant pressure corridor of 10-40 bar only at temperatures above 900 • C. Moreover, the production of syngas by DRM may be understood as the result of two competing processes, i.e., CO 2 and CH 4 activation. Coking may be considered unavoidable for a large set of operation conditions [56,76,77]. The effects on the reaction of increasing an external parameter while keeping constant the other ones are summarized in Table 4.…”
Section: Thermodynamics Of Drmmentioning
confidence: 99%
“…In general, these trends suggest that high conversions to syngas and representative H 2 /CO ratios are expected at the industrially relevant pressure corridor of 10-40 bar only at temperatures above 900 • C. Moreover, the production of syngas by DRM may be understood as the result of two competing processes, i.e., CO 2 and CH 4 activation. Coking may be considered unavoidable for a large set of operation conditions [56,76,77]. The effects on the reaction of increasing an external parameter while keeping constant the other ones are summarized in Table 4.…”
Section: Thermodynamics Of Drmmentioning
confidence: 99%
“…For instance Ni doped SrZrO 3 13,14 has been shown to resist coke formation significantly for model biogas with CH 4 /CO 2 = 2 and nickel hexaalumnates also show very good catalytic activity for dry reforming when the wt % of Ni is below a threshold value. 15 Although there are enough studies generally on dry reforming of CH 4 , the ones that study catalyst deactivation at typical biogas composition (CH 4 /CO 2 = 1.4−2.0) are rather limited. To the best of our knowledge, there are no studies yet on the catalyst deactivation due to simultaneous sulfur poisoning and carbon deposition during the dry reforming of biogas mixture.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There is evidence that the presence of a base metal in catalysts can suppress coke formation during both CH 4 decomposition and Bouduard reactions. Perovskite materials can also prevent the formation of carbon during dry reforming. For instance Ni doped SrZrO 3 , has been shown to resist coke formation significantly for model biogas with CH 4 /CO 2 = 2 and nickel hexaalumnates also show very good catalytic activity for dry reforming when the wt % of Ni is below a threshold value …”
Section: Introductionmentioning
confidence: 99%
“…As proven in previous papers, the BHA catalyst retains its activity even under extremely harsh reaction conditions due to its special geometric structure. 30,52 The XPS data provide evidence of the strong interaction between chemically distinct barium and alumina spinel block that leads to an increase in the catalytic activity of the BHA catalyst. DRIFT and TPD measurements showed that the surface of the BHA catalyst is enriched with acidic and basic sites that promotes the one-pot cascade decarboxylation and esterification reactions.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%